A standards-based architecture for grid service management - COGHLAN, BRIAN ARTHUR; KENNY, EAMONN; WALSH, JOHN (IEEE Computer Society Press, 2007)
Managing the availability of services is an essential task in ensuring the availability of a grid infrastructure. This project aims to take the next step in the monitoring and management of grid computing systems by developing a standards-based distributed control plane for grid resources and middleware components. While many existing projects focus on the monitoring of grid resources and infrastructures, they make little or no provision for the active or pro-active management operations required to ensure the availability of the infrastructure. This solution employs web service technologies with the intention of producing an extensible body of work that might be applied to a range of grid projects and middlewares. With the emergence of meta-grids and the increasing importance of grid middleware interoperability, the acceptance and adoption of standard interfaces will become an important step in the development of future grid components.
Keywords: Computer Science